The Influence of Organizational Experience on the Work Readiness of Office Administration Education Students (Pinisi Journal of Officers Review, 2024)
This study aims to determine the influence of organizational experience on the work readiness of students of the Office Administration Education Study Program, Department of Administrative Sciences, Faculty of Social Sciences and Law, Universitas Negeri Makassar. The population in this study is 53 students of the Office Administration Education Study Program. The data collection techniques used are observation, questionnaire and documentation. Meanwhile, the data analysis techniques used are descriptive statistical analysis using percentages, mean and standard deviations, data normality tests, product moment correlation analysis and simple linear regression analysis. The test results show that the indicators of the Organizational Experience variable are in the very high category, while the Work Readiness variable is in the very high category. Based on the results of the product moment correlation test, the influence between the two variables with a correlation coefficient of 0.799. So it can be concluded that there is a positive and significant influence between Organizational Experience on the Work Readiness of Students of the Office Administration Education Study Program, Department of Administrative Sciences, Faculty of Social Sciences and Law, Universitas Negeri Makassar. This study uses a different approach, namely quantitative descriptive and applies it to new areas.